Transformation or more of the same? The EU’s deforestation-free products regulation through a radical transformation lens - Verhaeghe, Elke; Ramcilovic-Suominen, Sabaheta (Elsevier, 2024)
The European Union (EU) is a major consumer of forest-risks commodities and therefore a key contributor to imported deforestation. In 2023, the EU Regulation on Deforestation-Free Products (EUDR) entered into force, which aims to counter the imported deforestation resulting from EU consumption of cattle, cocoa, coffee, palm oil, rubber, soy, wood and derived products. With this regulation, the EU is seemingly recognising its position as one of the world's largest consumers of natural resources and land-consuming agricultural products and adjusting its economy in the face of the global biodiversity, climate and planetary justice crises. In this article, we develop a radical transformation framework to put the EUDR to the test, asking to what extent the EUDR provides a truly transformative response to today’s planetary socio-ecological and justice crises. We develop a four-pronged radical transformation framework bridging insights from transformation, degrowth, Indigenous and decolonial environmental justice, restorative justice and science and technology studies. Concretely, we distil four tenets of radical transformation: onto-epistemic transformation, political transformation, economic transformation and judicial transformation. We apply our framework tentatively to the EUDR to illustrate its practical use, raise questions and highlight possible points of tension. Our preliminary findings point to the simultaneous existence in the EUDR’s design of elements potentially paving the way for counter-hegemonic (re)interpretations and uses on the ground and elements reflecting and reinscribing existing hegemonies.
Keywords: EUDR; due diligence; forests; justice; transformation